2014
DOI: 10.1016/j.semnephrol.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy in the Kidney: The Road More Traveled

Abstract: Summary Chaperone-mediated autophagy (CMA) is a lysosomal proteolytic pathway in which cytosolic substrate proteins contain specific chaperone recognition sequences required for degradation and are translocated directly across the lysosomal membrane for destruction. CMA proteolytic activity has a reciprocal relationship with macroautophagy: CMA is most active in cells in which macroautophagy is least active. Normal renal proximal tubular cells have low levels of macroautophagy, but high basal levels of CMA act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 93 publications
(160 reference statements)
2
17
0
Order By: Relevance
“…In this study, we examined the expression of LAMP2A in ten kinds of tumors, and found that LAMP2A was significantly upregulated in 8 kinds of human tumors, including lung cancer, breast cancer and gastric cancer, whereas, no significant increase was noticed in hepatic cell carcinoma and renal clear cell carcinoma, as its expression in normal liver cell and renal tubular cell was also very high. This is consistent with a previous finding, 27 supporting the notion that CMA is required for hepatic metabolism 24 and for proteostasis in renal tubular cells. 27 Nevertheless, our results strongly suggest that high CMA activity is a hallmark of malignancies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we examined the expression of LAMP2A in ten kinds of tumors, and found that LAMP2A was significantly upregulated in 8 kinds of human tumors, including lung cancer, breast cancer and gastric cancer, whereas, no significant increase was noticed in hepatic cell carcinoma and renal clear cell carcinoma, as its expression in normal liver cell and renal tubular cell was also very high. This is consistent with a previous finding, 27 supporting the notion that CMA is required for hepatic metabolism 24 and for proteostasis in renal tubular cells. 27 Nevertheless, our results strongly suggest that high CMA activity is a hallmark of malignancies.…”
Section: Discussionsupporting
confidence: 93%
“…3E), among which GAPDH, and PKM are well characterized CMA substrates, HSPA8 is the classic CMA chaperone, and PARK7/DJ-1 has been predicted to be a CMA substrate. 27 These proteins may help us to better understand the mechanisms through which CMA can regulate a range of biological pathways. We thoroughly examined our interactomic results, and found that RND3 was selected by KEGG analysis as a key regulator of the cytoskeleton, and its antiproliferative action has also been well characterized.…”
Section: Cma Is Required For Rapid Proliferation Of Gastric Cancer Cellsmentioning
confidence: 99%
“…This is determined by its degradation by two proteases, a metalloprotease that cleaves the protein inside the lysosomal membrane and cathepsin A, which cleaves the intralysosomal portion of the protein. To a lesser extent, LAMP-2A levels are also determined by synthesis [17]. Ageing leads to less stable LAMP-2A, resulting in lower levels of CMA activity [16].…”
Section: Chaperone-mediated Autophagymentioning
confidence: 99%
“…In cancer cells, CMA has been shown to be upregulated [20]. There is a functional reciprocal crosstalk between CMA and macroautophagy, as CMA is most active in cells in which macroautophagy is least active [17]. Inhibiting either one of these processes leads to upregulation of the other, thus providing a constant baseline autophagy level [6].…”
Section: Chaperone-mediated Autophagymentioning
confidence: 99%
See 1 more Smart Citation